Modulation of the Wound Healing through Noncoding RNA Interplay and GSK-3β/NF-κB Signaling Interaction - Xianyi Wang; Wanqiu Li; Shengdi Lu; Zhongliang Ma (International Journal of Genomics)
Diabetic foot ulcers are seriously endangering the physical and mental health of patients. Due to the long duration of inflammation, the treatment of nonhealing wounds in diabetes is one of the most prominent healthcare problems in the world. The nuclear factor kappa B (NF-κB) signaling pathway, a classical pathway that triggers inflammatory response, is regulated by many regulators, such as glycogen synthase kinase 3 beta (GSK-3β). Noncoding RNAs, a large class of molecules that regulate gene expression at the posttranscriptional or posttranslational level, play an important role in various stages of wound healing, especially in the stage of inflammation. Herein, we summarized the roles of noncoding RNAs in the NF-κB/GSK-3β signaling, which might provide new ideas for the treatment of diabetic wound healing.